Electrical Characterization of 65 W Cubic Sonoreactor with Horizontally Stacked Transducers - KERDTHONGMEE, Pansak; PHOLNAK, Chat; SIRISATHITKUL, Chitnarong; DANWORAPHONG, Sorasak (Archives of Acoustics, 2017)
A sonoreactor was assembled with stacked lead zirconate titanate transducers. These transducers were attached on one side of a 10×10×10 cm^3 chamber and driven by an integrated circuit power amplifier. The impedance of the reactor was analyzed in order to determine a matching inductance. The electrical frequency could be varied from 20 to 50 kHz and the electrical output power was adjustable up to 65 W. The highest power was obtained in the case of resonance at 31 kHz and the maximum temperature at the heat sink of the amplifier rose to 42.0°C. Both acoustic cavitation and mechanical effects could be utilized in this sonoreactor for a variety of purposes including sonochemical synthesis, ultrasonic cleaning and microbial cell disruption.